Que signifie « expérience de visite » pour le public enfant ? - Stéphanie Pinel-Jacquemin; Muriel Lefebvre; Julie Renard; Chantal Zaouche Gaudron (Communication)
This article begins by examining the semantic shift that has occurred between what used to be called a “museum visit” and is now known as a “visitor experience.” Drawing on a literature review conducted as part of a multidisciplinary research project on how young children appropriate the scientific tools made available by museums, the authors describe the various components that make up this experience, not only during the visit, but before and after as well.